Redeveloping the national innovative capacity framework: European Union perspective - Meda Andrijauskiene; Daiva Dumciuviene; Jovita Vasauskaite (Economies, 2021)
This paper aims to redevelop the national innovative capacity framework and specify the influence of its' elements on shaping the innovation performance of the EU nations. The objects of the empirical research are the EU member states for the period of 2000-2018. The collected data is employed in a multivariate Granger causality analysis that illustrates the causal links between the analyzed indicators and considers their dynamics. The results demonstrate that countries seeking to increase the levels of innovative outputs should mostly focus on scientific excellence and international economic activities. A redevelopment of the framework also helped discover that gender equality and corruption have causal links with all forms of the investigated innovation indicators-technological, non-technological, and commercial ones. The outcomes of this study highlight the most critical areas where EU member states could focus to improve their national innovation performance and may assist policymakers in the designing process of future innovation policies.
Keywords: 330; European Union; innovation; innovation performance; innovation policy; national innovative capacity